How Caspian Region Can Help Arctic Region? - YURIEVNA, Chernitsyna Sofiya (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).36, 2019)
The research compares the problems of two strategically important regions for Russia-the Caspian region and the Arctic region. Despite the fact that there are some significant geographical and climate differences, the geopolitical situation in the regions is similar. There are almost identical risks in the development of these regions. The main difference is that the Caspian region was exposed to the anthropogenic factor much earlier. The lessons learned from the work in the Caspian region can be used in the Arctic region, which can reduce some of the risks associated with the interaction of coastal countries.